AQUINAS’ CRITIQUE OF 13th CENTURY RADICAL APOCALYPTICISMS - Craine, Patrick (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2023)
The temptation to radical apocalypticism has plagued the Church in every age since the time of the apostles. Yet some moments, such as the recent COVID-19 crisis, are especially ripe for such tendencies. In the 13th century, Thomas Aquinas had to confront radical apocalypticism on two fronts: from the followers of Joachim of Fiore and from the mendicants’ opponents among the secular priests at the University of Paris. These confrontations gave Aquinas occasion to articulate a balanced approach to eschatology, rooted in Scripture and the tradition of the Fathers. In this paper, I examine Aquinas’ critique of radical eschatology in the context of a broader examination of his theology of history. Aquinas’ sober analysis, I maintain, can serve us well in confronting our own struggles with radical eschatologies.